Crystal structure of 7-(4-methylphenyl)imidazo[1,2-a][1,3,5]triazin-4-amine, C12H11N5 - Lim, F.; Dolzhenko, Anton; Halcovitch, N.; Tiekink, E. (R Oldenbourg Verlag, 2018)
© 2018 Felicia Phei Lin Lim et al., published by De Gruyter,Berlin/Boston. C 12 H 11 N 5 , monoclinic, P2 1 /n (no. 14), a = 7.3455(1) Å, b = 12.2470(1) Å, c = 12.1689(1) Å, ß = 103.505(1)°, V = 1064.45(2) Å 3 , Z = 4, R gt (F) = 0.0365, wR ref (F 2 ) = 0.0987, T = 100 K.